Transforming Marginalized Entrepreneurship: Digital Skills and Market Adaptability for MSMEs in Emerging Economies - Hamidi, Ichsan; Atiyatna, Dirta Pratama; Bashir, Abdul; Apriani, Deassy; Sani, Kamalia; Marissa, Feny (Pena Dimas: Jurnal Pengabdian Masyarakat, 2025)
With the rapid advancement of digital technology, Micro, Small, and Medium Enterprises (MSMEs) face both challenges and opportunities, particularly in emerging and disadvantaged economies. This case study explores a community-driven initiative designed to enhance the entrepreneurial capacity of MSMEs located around the Final Disposal Site (FDS) II Karya Jaya in Palembang, Indonesia, by integrating digital skill development with market adaptability. Using a Participatory Action Research (PAR) approach, thirty microenterprises—predominantly women-led—participated in a series of digital marketing workshops emphasizing problem-solving and co-design. Over twenty hours of training, participants developed entrepreneurial mindsets and competencies in social media and e-commerce, digital payment systems, branding, and packaging design. Observations indicated that 86.67% of participants demonstrated greater awareness of digital marketing tools, and 90% expressed increased confidence in their use. Follow-up monitoring with 22 participants revealed a 20% improvement in online visibility, engagement, and product identification. Beyond individual skill enhancement, the initiative strengthened social capital by fostering peer learning networks and cultivating local leadership, essential for sustainable community transformation. This initiative illustrates the transformative potential of digital empowerment practices to narrow the digital divide, enhance entrepreneurial resilience, and support inclusive and equitable economic growth. It aligns closely with several Sustainable Development Goals (SDGs), particularly SDG 1 (No Poverty) by improving livelihoods, SDG 5 (Gender Equality) through the empowerment of women entrepreneurs, SDG 8 (Decent Work and Economic Growth) via skill-based entrepreneurship, SDG 9 (Industry, Innovation, and Infrastructure) through digital inclusion, and SDG 10 (Reduced Inequalities) by integrating marginalized groups into the digital economy. Collectively, these outcomes demonstrate how digital literacy and community collaboration can accelerate sustainable development in disadvantaged urban areas.